The Macroeconomic Determinants and FDI: Evidence from 14 International Alliances - Paul, Sujan Chandra; Rosid, Md Harun Or; Islam, Mohammad Rakibul; Ferdous, Refat (Asian Development Policy Review, 2021)
This study investigates the relationship between Foreign Direct Investment (FDI) and some macroeconomic variables such as Gross Domestic Product (GDP), Gross Capital Formation (GCF), Agriculture, Forestry, and Fishing (AFF), Industry, Import, Export, Inflation and Unemployment rate. Panel Data of 14 regional alliances countries from 1990-2018 were collected from The World Bank website. Robust regression models are used in this study. This research found that GDP had significant positive relationship with FDI in all regions except Arab League, EU and G7 countries. GCF had significant positive relationship with FDI in Arab League, BRI, GATT, NAFTA countries & negative relationship in APEC, G7 countries. AFF had significant positive relationship with FDI in BRICS, GATT countries & negative relationship in African Union, ASEAN, BIMSTEC, BRI, BRICS, SAFTA countries. Industry had significant positive relationship with FDI in African Union, BRI, NAFTA, OECD countries and negative relationship in BRICS, G7, G20 countries. Import had significant positive relationship with FDI in African Union, APEC, Arab League, ASIAN, BRI, G7, G20, GATT countries and negative relationship in BRICS countries. Export had significant positive relationship with FDI in BRICS countries and negative relationship in African Union, ASEAN, BRI, G20, GATT, OECD, SAFTA countries. Inflation had significant positive relationship with FDI in GATT, SAFTA countries and negative relationship in African Union, APEC countries. Unemployment rate had significant positive relationship with FDI in African Union, BRI, BRICS, EU, G20, GATT, OECD, SAFTA countries and negative relationship in ASEAN countries.